# Properties of Addition of Matrices

1. Commutative Law of Addition of Matrix: Matrix multiplication is commutative. This says that, if A and B are matrices of the same order such that A + B is defined then A + B = B + A.

Proof:  Let A = [aij]m × n and B = [bij]m × n

Let A + B = C = [cij]m × n and B + A = D = [dij]m × n

Then, cij = aij + bij

= bij + aij , (by using the definition of addition of matrices)

= dij

Since C and D are of the same order and cij = dij then, C = D.

i.e., A + B = B + A. This completes the proof.

2. Associative Law of Addition of Matrix: Matrix addition is associative. This says that, if A, B and C are Three matrices of the same order such that the matrices B + C, A + (B + C), A + B, (A + B) + C are defined then A + (B + C) = (A + B) + C.

Proof: Let A = [aij]m × n ,B = [bij]m × n and C = [cij]m × n

Let B + C = D = [dij]m × n , A + B = E = [eij]m × n , A + D = P = [pij]m × n , E + C = Q = [qij]m × n

Then, dij = bij + cij , eij = aij + bij , pij = aij + dij and qij = eij + cij

Now, A + (B + C) = A + D = P = [pij]m × n

and (A + B) + C = E + C = Q = [qij]m × n

Therefore, P and Q are the matrices of the same order and

pij = aij + dij = aij + (bij + cij)

= (aij + bij) + cij , (by the definition of addition of matrices)

= eij + cij

= qij

Since P and Q are of the same order and pij = qij then, P = Q.

i.e., A + (B + C) = (A + B) + C. This completes the proof.

3. Existence of Additive Identity of Matrix: Let A be the matrix then, A + O = A = O + A

Therefore, ‘O’ is the null matrix of the same order as the matrix A

Proof: Let A = [aij]m × n and O = m × n

Therefore, A + O = [aij] + 

= [aij + 0]

= [aij]

= A

Again, O + A =  + [aij]

= [0 + aij]

= [aij]

= A

Note: The null matrix is called the additive identity for the matrices.

4. Existence of Additive Inverse of Matrix: Let A be the matrix then, A + (- A) = O = (- A) + A

Proof: Let A = [aij]m × n

Therefore, - A = [- aij]m × n

Now, A + (- A) = [aij] + [- aij]

= [aij + (- aij)]

= 

= O

Again (- A) + A = [- aij] + [aij]

= [(-aij) + aij]

= 

= O

Therefore, A + (- A) = O = (- A) + A

Note: The matrix – A is called the additive inverse of the matrix A.

Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.

## Recent Articles 1. ### Measuring Capacity | Standard Unit of Capacity | Litre | Millilitres

Nov 29, 23 01:15 AM

We will discuss about measuring capacity. The milkman measures milk in liters. Petrol is given in liters. Mobil oil is sold in liters. Two milk bottles contain 1 liter of milk. One milk bottle

2. ### Addition and Subtraction of Units of Measurement | Metric Units

Nov 29, 23 12:54 AM

We can add the units of measurement like decimal numbers. 1. Add 5 m 9 dm and 11 m and 5 dm Solution: 5 m 9 dm = 5.9 m 11 m 5 dm = 11.5 m Hence, 5 m 9 dm + 11 m 5 dm = 17 m 4 dm or 17.4 m 2. Add 15 cm…